Stress Analysis of Domestic Composite LPG Cylinder Using Classical Lamination Theory (CLT) - V K N S N Moorthy, CH; Srinivas, V (International Journal of Engineering and Technology, 2018)
Conventional Steel Cylinders used for LPG cylinder for domestic applications are not manufactured in a single joint but are welded. While composite cylinders are manufactured in a single joint, Composite components cannot be welded like the steel cylinder. Composite Cylinders are winded using Filament Winding technique. Compared to Steel Cylinders, Composite Cylinders are costlier. As composite cylinders are safer than steel cylinder, composite Cylinders due to a rubber lining inside, they are 100% leak proof. If mass production of composite cylinders are done then the cost may get reduced. This paper summarizes the design and analysis of the manufacturing of Liquid petroleum gas (LPG) Cylinder using Glass Fibre Reinforced Plastic (GFRP) material. The stresses along all the directions of the ply sequence are also calculated using Classical Lamination Theory (CLT).Â  The fibre stresses along all the directional angles were found to be under the required stress limits. The Metallic boss Calculation & angle variation at dome is the key parameter and is carried out and determined the tip radius.Â Â
Keywords: GFRP; Liquefied Petroleum Gas (LPG); Classical Lamination Theory (CLT); Tip Radius; Angle Variation at Dome